Performa Keuangan PT Krakatau Steel Tbk Sesudah 12 Tahun IPO - Sucipto, Rakhmat Hadi (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2024)
Many companies change their status from closed companies to public companies by releasing initial shares (IPO) to the public, including steps taken by PT Krakatau Steel (Persero) Tbk. This step can create both positive and negative effects. This study seeks to examine the effect of the IPO on the company's financial performance. The financial ratio of businesses that choose to become public companies is the focus of this study in particular. This study uses secondary data from the company to develop quantitative method analysis. The current ratio, quick ratio, debt to equity ratio, return on equity, return on assets, and debt to asset ratio are the main subjects of the investigation and analysis. According to the analysis's findings, the current ratio, debt to equity ratio, and debt to asset ratio are all significantly impacted negatively by the company's decision to become public. Return on equity, return on assets, and quick ratio are unaffected by changes in the company's status.